Adenomyosis and infertility. Management strategies - A.E. Esedova; A.M. Medzhidova (LCC «Medicine-Inform», 2021)
A.E. Esedova, A.M. Medzhidova Dagestan State Medical University, Makhachkala, Russian Federation Aim: to improve the rate of pregnancy in women with adenomyosis and infertility. Patients and Methods: this prospective comparative study included 150 women aged 24-38 years. Among them, 120 women were diagnosed with infertility and adenomyosis, and 30 healthy women planned pregnancy (control group). 60 women (study group 1) underwent surgery for adenomyosis, 30 women were followed up only (study subgroup 1A) and 30 women received Dienogest 2 mg for 6 months (study subgroup 1B). Women of study group 2 (n =60) underwent no surgery, 30 women were followed up only (study subgroup 2A) and 30 women received Dienogest 2 mg for 6 months (study subgroup 2B). After 3 and 6 months, blood levels of hormones, junctional zone thickness (measured by ultrasound), and the rate and time of pregnancy were assessed. Results: at baseline, women with adenomyosis were reported to have high levels of estradiol (p<0.05 compared to the control group). After 3 and 6 months, the level of es tradiol gradually reduced to 432.5±27.4 pmole/l and 364.3±16.2 pmole/l in study subgroup 2A and 314.3±22.7 pmole/l and 264.7±18.6 pmole/l in study subgroup 2B (p<0.05). Pregnancy occurred, on average, after 6.1±1.6 (3-8) months in study subgroup 1A, 5.3±1.1 (4-7) months in study subgroup 2A, 4.1±1.4 (2-7) months in study subgroup 1B (p≤0.05 compared to study subgroup 1A and study group 2), and 5.1±1.2 (3-7) months in study subgroup 2B. In study groups 1 and 2, pregnancy occurred 1.5- and 1.4-times more commonly in women who received Dienogest. Conclusions: surgery and further hormone therapy is an optimal management strategy for adenomyosis and infertility. Keywords: adenomyosis, infertility, Dienogest, junctional zone, pregnancy. For citation: Esedova A.E., Medzhidova A.M. Adenomyosis and infertility. Management strategies. Russian Journal of Woman and Child Health. 2021;4(2):110-114. DOI: 10.32364/2618-8430-2021-4-2-110-114.